Inhibitory effect of essential oils on growth and ochratoxin a production by penicillium species - Rao, Vankudoth Koteswara; Sivadevuni, Girisham; Reddy, Solipuram Madhusudhan (Research Journal of Microbiology, 2015)
The screening of essential oil of brassica (Brassica oleracea), castor (Ricinus communis), coconut (Cocos nucifera), eucalyptus (Eucalyptus globulus), groundnut (Arachis hypogaea), neem (Azadirachta indica), palmolive (Elaeis guineensis) and sunflower (Helianthus annuus) for their efficacy against growth and OTA production by P. verrucosum and P. nordicum was performed. Neem and eucalyptus oil were most effective inhibitors of biomass and OTA production by both the species of Penicillium under investigation. P. nordicum was totally inhibited at 15 µL mLG1 concentration of neem and eucalyptus oil, while P. verrucosum was inhibited only to the extent of 77.52-92.49%. Sunflower and palmolive oils were next in their toxicity against the growth and OTA production by both the species of Penicillium under investigation. Essential oil of brassica, castor, coconut and groundnut varied in their degree of inhibition against P. verrucosum and P. nordicum. A positive correlation coefficient (R) was observed between the inhibitory effect of essential oils on growth (0.8933) and OTA production (0.9242). In conclusion, neem and eucalyptus oils proved to be potential bio-control agents and help to prevent the infestation of stored foods and feeds by 2 species of Penicillium and elaboration of OTA